New record of the Andean cat in the Puna of Jujuy province, north-western Argentina - Gonzalez, Francisco Rodrigo (2017)
In the last decade, there has been a remarkable growth in the knowledge of thehabits and behaviour of the Andean Cat Leopardus jacobita. This cat is mainly restrictedto the Andean highlands. Most of the records from north-western Argentinaare based on indirect evidences. We provide a new record from Jujuy provincebased on photographs and a video of one of two cats seen in this area. We observedthe cat moving across rocky outcrops exhibiting a hunting behaviour during daylighthours. This filmic record is a valuable contribution for the promotion of theconservation of this species.